Future skills in education : knowledge management, AI and sustainability as key factors in competence-oriented education - Golowko, Nina (Sustainable Management, Wertschöpfung und Effizienz,, 2021)
This book identifies central key factors for future-oriented teaching in Higher Education to support the task of ensuring the knowledge transfer for sustainable and competence-oriented employability to the future workforce. Through an innovative approach using machine-learning algorithms that employ the universities own and extern databases as knowledge base, new perspectives for the development of competence-oriented curricula and study programmes in Higher Education are shown. About the author Dr. Nina Golowko has been an entrepreneur and lecturer in general business administration at several private and public universities in the Rhine-Main area for 20 years. Her teaching focuses in particular on accounting & controlling, mathematics and digitalization, with a specific emphasis on interdisciplinary approaches.